The Emergence of Employees’ Change Readiness for Energy-Conservation Behavior During Guided Group Discussions - Güntner, Amelie Verena; Endrejat, Paul Constantin; Kauffeld, Simone (Frontiers in Psychology, 2021)
Compared to studies in the residential sector, energy-conservation in organizations is an aspect that has not received as much attention as it deserves to reduce CO2 emissions. To increase employees' readiness for changing their behaviors in favor of energy-conservation, we focus on the use of guided group discussions (GGDs) and rely on observational research methods to examine the micro-level of behavioral dynamics and understand the emergence of change readiness. We describe how change agents can facilitate GGDs and foster employees' change readiness using the established communication approach Motivational Interviewing. Second, we explore how employees' can raise each other's change readiness regarding energy-conservation behavior. In a sample of eight videotaped GGDs (5430 behavioral events) interaction analysis showed that agent's solution-focused communication elicited employees' change readiness, whereas a problem-focused communication evoked employees' resistance to change. We further showed that employees themselves can motivate their co-workers for “green” intentions by verbalizing statements in favor (against) energy-saving to increase (decrease) other employees' change readiness. In doing so, we also consider GGD participants as active individuals that can create behavior change in their co-workers. Further, we derive communication guidelines for working with groups and discuss the importance of solution-focused energy management practices to facilitate change readiness for saving energy in the workplace.